Humanitarian logistics: An approach to the supply from agroindustrial food chains (2014)
The growth of world food production and the poor distribution of them is analyzed and discussed. The subject is treated considering that the appropriate distribution of food is of paramount importance and proposes a methodology based on mechanics of materials to assist in the decision making process. Food production has increased in many countries, but the number of people has also increased and food distribution has not improved according to the increase in people and foods. Additionally, the food chain is nowadays more vulnerable to environmental pollution. The proposed methodology is based primarily on the establishment of the necessary measures to ensure access to an adequate amount of food, in this chain of humanitarian logistics. The paper concludes with a description of challenges and opportunities for better distribution of food in the world, today and in the future.